2020
DOI: 10.1186/s12929-020-00646-x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant lipidated Zika virus envelope protein domain III elicits durable neutralizing antibody responses against Zika virus in mice

Abstract: Background: The emergence of Zika virus (ZV) in tropical and subtropical areas of the world has created an urgent need for vaccines against ZV. However, approved vaccines that prevent ZV infection are not available. To develop an effective vaccine against ZV infection, a lipidated form of ZV envelope protein domain III that possesses an intrinsic adjuvant property was rationally designed. Our goal was to examine the immunogenicity of recombinant lipidated ZV envelope protein domain III (rLZE3) and evaluate its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Our previous studies showed that recombinant lipidated proteins containing domain 3 of the envelope protein of dengue virus can enhance both antibody titers and neutralizing antibody titers [ 38 , 39 ]. Similar effects were observed with lipidated domain 3 of the envelope protein of the Zika virus [ 40 ]. We previously identified the B cell epitope of TAL6 that can induce ADCC to kill cancer cells [ 21 ].…”
Section: Discussionsupporting
confidence: 72%
“…Our previous studies showed that recombinant lipidated proteins containing domain 3 of the envelope protein of dengue virus can enhance both antibody titers and neutralizing antibody titers [ 38 , 39 ]. Similar effects were observed with lipidated domain 3 of the envelope protein of the Zika virus [ 40 ]. We previously identified the B cell epitope of TAL6 that can induce ADCC to kill cancer cells [ 21 ].…”
Section: Discussionsupporting
confidence: 72%
“…Construction of the pOVA, pOVA-FLIPr and pZEIII expression vectors has been described previously ( 40 , 48 ). The DNA sequence of ZEIII-FLIPr was synthesized (Purigo Biotechnology Co., Taipei, Taiwan) using E. coli codon usage according to the amino acid sequences of Zika virus PRVABC59 (accession number AMC13911) and FLIPr (accession number BAB57318).…”
Section: Methodsmentioning
confidence: 99%
“…The production and purification of rOVA, rOVA-FLIPr, and rZEIII was described previously ( 40 , 48 ). For the expression of rZEIII-FLIPr, pZEIII-FLIPr was transformed into E. coli BL21 (DE3) (Lucigen, Middleton, WI).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations